Construction and monitoring of experimental straw bale building in northeast China. (20th September 2018) - Yin, Xunzhi; Lawrence, Mike; Maskell, Daniel; Chang, Wen-Shao
Highlights: Designs of straw bale construction in context with climatic conditions in northeast China. Effectiveness of the designs are justified through the construction of a experimental building and the following monitoring research. Care should be taken in preventing condensation within straw bales during the periods which temperature fluctuates around freezing point. Abstract: Straw bale buildings have the potential reduce the environmental impact of construction. Although the technique has been introduced into northern China more than a decade ago, the construction method and potential problems within straw bale walls have not been fully understood in existing research. Following an analysis of existing straw bale construction both in north China and worldwide, this paper proposes modifications to the straw bale construction details currently used in north China. The modifications involve in-fill raw material, toe-up design and lime render application. These modifications were incorporated into an experimental building constructed in north China, and after having been monitored for 12 months, the modified construction details were critically assessed. The data demonstrate that rice straw bale walls are resistant to agents of decay and offer reduced construction time and cost than standard wall construction in north China. The construction method has the potential to become a mature construction system in the Chinese market in the future offering significant benefits both in construction and operational cost and in environmental impact.